2018
DOI: 10.1111/1750-3841.14175
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Wheat Derived Nonspecific Lipid Transfer Protein 2 (nsLTP2)

Abstract: Numerous studies support the protective role of bioactive peptides against cardiovascular diseases. Cereals represent the primary source of carbohydrates, but they also contain substantial amounts of proteins, therefore representing a potential dietary source of bioactive peptides with nutraceutical activities. The analysis of wheat extracts purified by chromatographic techniques by means of HPLC-UV/nanoLC-nanoESI-QTOF allowed the identification of a signal of about 7 kDa which, following data base searches, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In fact, the content of bioactive peptides is largely different in different cereals and cereal-derived foods. The analysis of different wheat extracts purified by chromatographic techniques allowed the identification of non-specific lipid-transfer protein type 2 (nsLTP2) from Triticum aestivum [ 8 ]. This peptide is chemically thermo- and protease-resistant.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the content of bioactive peptides is largely different in different cereals and cereal-derived foods. The analysis of different wheat extracts purified by chromatographic techniques allowed the identification of non-specific lipid-transfer protein type 2 (nsLTP2) from Triticum aestivum [ 8 ]. This peptide is chemically thermo- and protease-resistant.…”
Section: Introductionmentioning
confidence: 99%
“…turanicum) [19]. In a previous study we demonstrated the antioxidant/cytoprotective activity of nsLTP2 in the same experimental model [20]. Since oxidative stress and inflammation represent the basis of endothelial dysfunction, these activities could be considered as potentially beneficial for vascular health maintenance.…”
Section: Discussionmentioning
confidence: 88%
“…Afterwards, inflammatory stress was induced using the inflammatory cytokine TNF-α (20 ng/mL). The 10nM concentration of nsLTP2 was chosen because it has been previously demonstrated to exert antioxidant and cytoprotective effects in HUVECs following oxidative and inflammatory stimulation [20].…”
Section: Cells Culture and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations